Helicobacter pylori Infection and Its Risk Factors: A Prospective Cross-Sectional Study in Resource-Limited Settings of Northwest Ethiopia - Markos Negash; Habtamu Wondifraw Baynes; Demeke Geremew (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. Helicobacter pylori (H. pylori) is implicated for the causation of gastrointestinal tract infections including gastric cancer. Although the infection is prevalent globally, the impact is immense in countries with poor environmental and socioeconomic status including Ethiopia. Epidemiological study on the magnitude of H. pylori and possible risk factors has priceless implication. Therefore, in this study, we determined the prevalence and risk factors of H. pylori infection in the resource-limited area of northwest Ethiopia. Methods. A prospective cross-sectional study was conducted on northwest Ethiopia among 201 systematically selected dyspeptic patients. Data were collected using a structured and pretested questionnaire, and stool and serum samples were collected and analyzed by SD BIOLINE H. pylori Ag and dBest H. pylori Disk tests, respectively. Chi-square test was performed to see association between variables, and binary and multinomial regression tests were performed to identify potential risk factors. P values <0.05 were taken statistically significant. Result. Prevalence of H. pylori was found to be 71.1% (143/201) and 37.3% (75/201) using the dBest H. pylori Test Disk and SD BIOLINE H. pylori Ag test, respectively. H. pylori seropositivity, using dBest H. pylori Disk tests, is significantly associated in age groups <10 years (P=0.044) and married patients (P=0.016). In those patients with H. pylori (a positive result with either the Ab or Ag test), drinking water from well sources had 2.23 times risk of getting H. pylori infection (P=0.017), and drinking coffee (1.51 (0.79–2.96, P=0.025)) and chat chewing (1.78 (1.02–3.46, P=0.008) are the common risk factors. Conclusion. The present study discovered considerable magnitude of H. pylori among the dyspeptic patients in the study area. H. pylori infection is frequent in individuals drinking water from well sources, and thus, poor sanitation and unhygienic water supply are contributing factors. Policies aiming at improving the socioeconomic status will reduce potential sources of infection, transmission, and ultimately the prevalence and incidence of H. pylori.